2015
DOI: 10.1007/s00262-015-1730-4
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 tolerance is independent of the type I IFN pathway and leads to loss of anti-tumor efficacy in mice

Abstract: Systemic administration of small molecule toll-like receptor (TLR)-7 agonists leads to potent activation of innate immunity and to the generation of anti-tumor immune responses. However, activation of TLRs with small molecule agonists may lead to the induction of TLR tolerance, defined as a state of hyporesponsiveness to subsequent agonism, which may limit immune activation, the generation of anti-tumor responses and clinical response. Our data reveal that dose scheduling impacts on the efficacy of systemic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For the one, SC1 dosing releases considerably higher levels of the therapeutically relevant IFNα. Second, whereas other TLR7 agonists have been reported to render the IFN response refractory and thus induce strong tachyphylaxis, [22][23][24] we showed that each dosing of a 5-daily repeat-drug regimen with SC1 is still capable of inducing a substantial IFNα serum peak. Third, further extending previous reports, 20 we showed that distinctively SC1 was not associated with release of pyrogenic cytokines, e.g., IL6, TNFα, MIP1β.…”
Section: Discussionmentioning
confidence: 71%
“…For the one, SC1 dosing releases considerably higher levels of the therapeutically relevant IFNα. Second, whereas other TLR7 agonists have been reported to render the IFN response refractory and thus induce strong tachyphylaxis, [22][23][24] we showed that each dosing of a 5-daily repeat-drug regimen with SC1 is still capable of inducing a substantial IFNα serum peak. Third, further extending previous reports, 20 we showed that distinctively SC1 was not associated with release of pyrogenic cytokines, e.g., IL6, TNFα, MIP1β.…”
Section: Discussionmentioning
confidence: 71%
“…Systemic administration of DSR-6434 may reinforce the effect of radiation therapy of cancer in mouse models. However, upon administration twice a week, TLR tolerance emerged and no anti-tumor activity was observed compared with administration once a week, suggesting that activation of DSR-6434 occurs in a dose-dependent manner (Nakamura et al, 2013; Adlard et al, 2014; Koga-Yamakawa et al, 2015). Analogous molecules such as DSR-29133 also have similar potential and the anti-tumor effects can be fortified by combining with low-dose fractionated radiation therapy (Dovedi et al, 2016).…”
Section: Other Agonistsmentioning
confidence: 99%
“…20 In contrast, in a murine study, intravenous administration of a TLR7 agonist resulted in the down modulation of TLR7, which corresponded to a decreased induction of IFNα following a subsequent dose of a TLR7 agonist and reduced efficacy when dosing was twice weekly compared with weekly. 29 In this study, the tolerising effect on TLR7 was independent of type I IFN and may well reflect differences in the dose and dosing regimen. In our study, weekly dosing was with a TLR7 agonist at doses that were only just showing significant induction of IFN-inducible markers, whereas the murine study was using a dose that was giving near maximal TLR7 stimulation.…”
Section: Discussionmentioning
confidence: 78%